The Effect of Phytase and Saccharomyces cervisiae (Sc47) Supplementation on Performance, Serum Parameters, Phosphorous and Calcium Retention of Broiler Chickens - Ghasemi, H.A.; Tahmasbi, A.M.; Moghaddam, Gh.; Mehri, M.; Alijani, S.; Kashefi, E.; Fasihi, A. (International Journal of Poultry Science, 2006)
An experiment was performed to assess the potential of microbial phytase and Saccharomyces cervisiae (Sc47) on improving the utilization of phytate P and subsequently on broiler performance fed wheat-corn-soybean meal basal diet from 7 – 49 day of age. A 3x2x2 factorial arrangements of treatments were used: 3 levels of Sc47 (0.0, 0.1 and 0.2 % of diet); two levels of phytase (0 and 800 U / kg of diet) and two levels of nonphytate P (50% and 100% of NRC (1994) recommended). Each treatment contained 3 pens with 15 birds/pen. Measurements included body weight gain (BWG), feed conversion ratio (FCR), serum parameters, Tibia ash, P and Ca retention. During the experimental periods effects of Non phytate phosphorous (NPP) levels on all measured parameters was significant (P< 0.01). Phytase inclusion at 800 U/kg of diet induced improvement (P< 0.05) in BWG, FCR, tibia ash, P and Ca retention and also increased concentration of serum P and protein (p< 0.05). Inclusion phytase on the diet containing the 50% NRC (1994) NPP resulted improvement on the utilization of phytate P and Ca by increasing P and Ca retention which led to an increase in toe ash content. The experiment demonstrated dietary supplementation of Saccharomyces cervisiae had a positive influence on the bird`s performance. However, significant improvement (P< 0.05) was observed in BWG and FCR during starter phase in chickens fed the diets containing Saccharomyces cervisiae. Maximum responses to live yeast achieved when broiler chicks were fed diet with 100% NRC (1994) recommended available phosphorous. In conclusion, the finding of this study suggested combination of supplemental phytase and live yeast (Sc47) had some beneficial effects on improving the nutritive value of broilers diets in particular in the low level of NPP.